Anti-metastatic effect of curcumin analog pentagamaboronon-0-fructose (PGB-0-F) against 4T1 breast cancer cells - Yogi Ertanto; Rohmad Yudi Utomo; Riris Istighfari Jenie; Ratna Asmah Susidarti; Edy Meiyanto (Indonesian Journal of Biotechnology, 2018)
Development of a chemotherapeutic agent and boron carrying pharmaceutical based on triple-negative breast cancer is important due to its metastatic progression. Metastases are often more dangerous than the primary tumor and they are responsible for 90% of all cancer deaths. The purpose of this study was to explore the anti-metastatic activities of the PGB-0 complex with fructose (PGB-0-F) against 4T1 breast cancer cells. A scratch wound healing assay was carried out to determine the migration inhibition ability of PGB-0-F, while MMP-9 expression was analysed using gelatin zymography. The testing of anti-migration activity showed that PGB-0-F inhibited in 4T1 cells, whereas the gelatin zymography assay revealed a suppression of MMP-9 expression. PGB-0-F inhibited closure on 4T1 metastatic breast cancer cells line compared with the control. PGB-0-F decreased the MMP-9 expression level compared with the control. Based on these results, PGB-0-F has the potential to be developed as a chemotherapeutic agent, and especially as an anti-metastatic agent.